Comunicação performativa do corpo: fazer-dizer da contemporaneidade - Setenta, Jussara Sobreira (2006)
In public communication, the body currently encounters a kind of overexposure by the media that can be seen as a frame to be confronted if the principle intent is to not participate in the media process as such. Although it may seem to a averagely attentive person that we live in a time where the body has become one of the most explored of subjects, those who reflect upon contemporary culture call attention to the fact that this highly exposed, mediated body is always behind the same type of filters. In certain cultural areas, the body chooses other forms of communication and, in challenging the hegemonic images of mass culture, is by them confined to peripheral niches. Contemporary dance is one such peripheral niche. The hypothesis that resulted in the research herein presented as a doctoral dissertation was developed out of the speech acts theory of J. L. Austin, regarding verbal language, which was extended to body language by placing its formulations in dialogue with the corpomídia [body-media] theory developed by Katz & Greiner (1999, 2000, 2001, 2004, 2005), as well as with works of critics of culture such as Negri (2004, 2005) and Foucault. Proposing that the body is corpomídia of contemporaneity in installing other forms of behavior, the hypothesis is that this happens when its saying initiates its doing. This doing-saying distinguishes human and institutional bodies. Based on the theoretical frame here presented, this dissertation investigates the relationship between the Dance School of the Federal University of Bahia and the dance companies it produced. Could they be considered as corposmídia of the institution that created and supported them? The research also deals with the question of the visibility/ invisibility of contemporary dance itself, understood here as a sub-product of the cultural journalism practiced in Brazil